Seed treatment strategies combining Bacillus amyloliquefaciens and insecticides for management of the emerging soil pest Scutigerella immaculata in soybean - Santos, Adilson Moraes; Sobrinho, João Batista Coelho; Nuñez, Yamile Salvatierra; Silva, Luciana Barboza; Oliveira, Matheus Henrique dos Santos; Ramos, Allison Samara Zabala; Ulhoa, Lucas Adjuto; Pereira, Jardel Lopes; Ferreira, Luiz Leonardo; Pereira, Alexandre Igor Azevedo (Journal of Plant Protection Research, 2026)
Scutigerella immaculata (Symphyla: Scutigerellidae) causes increasing problems in soybean-producing areas of Brazil, particularly in MATOPIBAPA, one of the country’s most recent agricultural frontiers. This study evaluated soybean seed treatments for the control of S. immaculata, using Bacillus amyloliquefaciens applied alone or combined with chemical insecticides, and assessed pest sampling methods and soybean responses to these treatments. Soybean seeds were treated on the day of planting in the municipality of Açailândia, Maranhão State, Brazil. The experiment was conducted under field conditions in a completely randomized design with nine treatments and four replicates. The treatments (T) were T1: untreated control, T2: fipronil, T3: bifenthrin + imidacloprid, T4: clothianidin, T5: B. amyloliquefaciens, T6: clothianidin + fipronil, T7: clothianidin + lambda-cyhalothrin, T8: clothianidin + fipronil + B. amyloliquefaciens, and T9: cyantraniliprole + lambda-cyhalothrin + thiamethoxam + abamectin. S. immaculata was sampled using potato baits placed in the soil and by direct counting on plant roots. Evaluated parameters included plant height, seedling emergence, seed germination, and fresh root and shoot mass, which showed significant differences among treatments. Direct counting on plant roots detected more individuals than bait sampling. Among the treatments, T7 resulted in the lowest mean number of S. immaculata individuals. Pest population peaks occurred between 60 and 90 days after planting. Further studies are needed to clarify the effectiveness of the evaluated biological product and to determine the contribution of soybean seed treatment to the control and integrated management of this emerging pest.